Kombinasi Teori Manajemen Ilmiah dan Pendekatan Humanis : Implementasi di IAIN Curup - Revi Permanasari; Sutarto Sutarto; Syaiful Bahri (Berkala Ilmiah Pendidikan, 2024)
This study examines the implementation of a combination of scientific management theory and humanistic approach at IAIN Curup to enhance operational efficiency and employee well-being. Scientific management theory, developed by Frederick Taylor, emphasizes efficiency, standardization of procedures, and clear division of tasks, while the humanistic approach proposed by Henry Gantt highlights the importance of employees' social and psychological well-being and their involvement in decision-making processes. This research employs a descriptive qualitative approach with observations, in-depth interviews, and document analysis in the finance, planning, and staffing departments at IAIN Curup. The findings indicate that the combination of these two theories successfully creates a productive work environment that supports employee well-being. Standardized procedures improve efficiency and data accuracy, while the humanistic approach fosters motivation, participation, and employee loyalty. Challenges in implementing this combination include adaptation to new methods and balancing efficiency with well-being. The implications of this study highlight the importance of balanced management practices in improving the performance of educational institutions.